The Impact of Online Teaching during the Coronavirus Pandemic on the Lives of Teachers and Parents - Zaidi, Kashaf Aqeel; Gul, Afreenish; Ahmad, Farah (Asian Journal of Education and Training, 2020)
To assess the degree of stress among teachers and parents of children taking online classes during the coronavirus pandemic. This was a cross-sectional study conducted in October 2020. An online questionnaire developed on Google Forms was circulated using convenience sampling technique with a sample size of 384. The target population included teachers and parents of children taking online classes. An informed consent was taken prior to the survey. The Perceived Stress Scale was used to evaluate the stress related to online teaching. Chi square test was applied to identify associations and a p-value of less than 0.05 was taken as significant. Our sample included 414 participants with n=359 (86.7%) females and n=55 (13.3%) males. N=156 (37.7%) participants were parents and n=258 (62.3%) were teachers. Majority of the participants had moderate perceived stress with n=193 (74.8%) teachers and n=127 (81.4%) parents. Teachers felt more comfortable going back to school right now n=176 (80.7%), whereas, only n=42 (19.3%) parents felt comfortable sending their children back to school. (p-value=0.000) After the pandemic resolves, parents preferred classroom learning n=111 (44.6%) while n=113 (75.3%) teachers preferred a hybrid system with both online and classroom learning. (p-value=0.001). Majority of the teachers and parents were found to be in moderate perceived stress. An increase in working hours for teachers and increase in the required supervision time for parents were among the most common causes.